Review of CICERO, Opera omnia, Ed. Andreas Cratander, Basel 1528, With an introductory essay by C. SCHEIDEGGER LÄMMLE & G. MANUWALD - Reggi, Giancarlo (Ciceroniana On Line, 2023)
Cicero, Opera omnia, Ed. Andreas Cratander, Basel 1528, Reproduction of the copy of the University Library in Basel. With an introductory essay by / Reproduktion des Exemplars der Basler Universitätsbibliothek. Mit einer Einführung von Cédric Scheidegger Lämmle und Gesine Manuwald, Schwabe, Basel 2022 (3 Bände), ISBN 978-3-7965-4343-2.